Keputusan Pembelian Makanan Tradisional Kacang Pukul di Rokan Hilir - Sari, Yulianda (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Micro, Small and Medium Enterprises (MSMEs) have a very strategic role in the national economy, because they touch the interests of people’s lives widely. Therefore, MSMEs are the backbone of our country’s economy. One example of MSMEs in Rokan Hilir Regency is HH brand peanuts. The purpose of this study is to answer the 3 hypotheses that have been made. Quantitative research was conducted by involving consumers of HH brand peanut products. The questionnaire was distributed using Google Form and SEM-PLS analysis was carried out. The research findings obtained that there was a positive and significant relationship between Price (X1) and Purchasing Decisions (Y). In addition, there was a positive and significant relationship between product quality (X2) and purchasing decisions and there was a positive and significant relationship between Brand (X3) and purchasing decisions (Y).